2017
DOI: 10.53553/jch.v05i02.005
|View full text |Cite
|
Sign up to set email alerts
|

Infant and Young Child Feeding Practices among Tribal Population of a Tea Estate in Darjeeling District, West Bengal, India

Abstract: Background: Infant and Young Child Feeding (IYCF) practices play an instrumental role in the social and in turn the individual aspect of human life for promotion of good growth, health, behaviour and cognitive development of the child. Objectives: To find out the current Infant and Young Child Feeding Practices and their correlates among tribal children aged 0-23 months residing in a tea garden of Darjeeling district, West Bengal. Methods: A community-based cross-sectional descriptive study was undertaken amon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 6 publications
1
1
0
Order By: Relevance
“…This study revealed that the mean IIFAS scores were (54.88 ± 3.38) for the intervention and (52.53 ± 3.07) for the control, which is within a range reflecting a neutral attitude towards breastfeeding. The findings of the current study are in congruence with similar findings from Ethiopia [20] and other countries, including China [19], Italy [39], and India [7,40]. However, this study is contrary to the study conducted in Australia, which had a positive IIFAS score [41].…”
Section: Plos Onesupporting
confidence: 87%
See 1 more Smart Citation
“…This study revealed that the mean IIFAS scores were (54.88 ± 3.38) for the intervention and (52.53 ± 3.07) for the control, which is within a range reflecting a neutral attitude towards breastfeeding. The findings of the current study are in congruence with similar findings from Ethiopia [20] and other countries, including China [19], Italy [39], and India [7,40]. However, this study is contrary to the study conducted in Australia, which had a positive IIFAS score [41].…”
Section: Plos Onesupporting
confidence: 87%
“…There is strong evidence that human milk feeding decreases the incidence and severity of a wide range of infectious diseases [4]. Maternal/caregiver breastfeeding knowledge, attitude, and self-efficacy are the main influencers on a child's nutritional status [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…The factors that may contribute to poor CF have been the subject of several research. For instance, a study conducted in Nepal and West Bengal, India indicated that maternal employment, education, age, income and media exposure as determinants of suboptimal CF [4,5]. Whereas inadequate knowledge, illiteracy, and poverty were the main causes of suboptimal CF in rural Bangladesh [6], mother self-efficacy in Iran [7] and knowledge in Ghana [8], were the main causes of suboptimal CF.…”
Section: Introductionmentioning
confidence: 99%